Pedagogia da dialogicidade: resson??ncias gen??ticas, intertextuais e discursivas em Pedagogia do Oprimido (o manuscrito) - Lauriti, N??dia Concei????o (2018)
In this thesis, the principle of dialogicity, as a vector of Freirian thought, is examined in the facsimile publication of the manuscript of "Pedagogy of the Oppressed", author's work, whose analysis, for its implicit canonicity of document value can contribute to the understanding of the genesis of his theory. This principle is discussed in this context, with the following objectives: a) to contribute to the explanation of potential meanings that can be enriched by the confrontation of the cross temporalities present in the work; b) demonstrate the three-dimensional nature of Freirian dialogue as the basis of its ontological, epistemic and methodological propositions; c) identify the marks of the manuscript as essay writing and the "process documents" of a literary work Marco Lucchesi as an inventive writing; and d) demonstrate, in the manuscript, the intersection of two discursive worlds - the educational and the political - from which emerges the double freirian ethos. It is a qualitative research of theoretical-analytical nature based on contributions derived primarily from discourse analysis and genetic criticism. In this seminal text, we find intratextual, intertextual and paratextual clues that reveal the protagonism of the operative principle of dialogicity in three complementary dimensions that serve as analytical perspectives, namely: the way of saying ("modus dicendi") revealing the substitutionary , exchange, addition, and elimination covered by the erasures that give visibility to the internal dialogic relations through which the "scriptor" discusses with his writing; the way of showing ("modus mostrandi") exposed by the intertextual apparatus and the paratextual constituents that compose the work, portraying the memory of the text, enriching its potential hidden meanings by the folds of time and changing the sensitive conditions of its reception to the reader of the XXI century; and the way of acting in the discourse ("modus faciendi") on which Freire's dual political-pedagogical ethos is based, establishing him as a pioneer of educommunication in Brazil. In the manuscript the matrix embryo of what could be denominated "Pedagogy of the educational dialogue", wielded with the oppressed and not for the oppressed, was verified in the manuscript. Thus, in this investigation, the hypothesis was confirmed that the freiriana dialogic inscribed in the manuscript is a multidimensional operative principle that crosses every conceptual field of the work, revealing itself as a singular gesture that goes beyond the linguistic field to install itself in the discursive dimension and pragmatic approach to language. It is a regulating principle that models his saying, his show and his action in the discourse and in the world, underpinning the other categories. This principle implied a broad and comprehensive view of the human being and did not focus only on the dialogue- denunciation of the situation of the oppressed, but mainly the announcement of possible ways of reversing this circumstance. This research also revealed the principle of Freirean dialogue as a significant indicator of his creative gesture, of the moving thinking of a Freire "writer", that is, of someone who lived and experimented dialogically with the concepts created based on his praxis.